Possibilities of selection and production of blue and ornamental corn (Zea mays L.) - Bódi, Zoltán; Pepó, Pál (Acta Agraria Debreceniensis, 2006)
The cultivation of alternative crops has an important role in world agriculture. Their market share is continuously growing in the food industry sector. In the present study, we show the cultivation and breeding perspectives of ornamental and blue corn. There exists possibility to cultivate ornamental corn in Hungary. There are many cultivars of ornamental corn, with various kernel colors, husks, stalks and leave colors. Blue corn is unique among other corns. Blue corn higher in protein, iron and zinc than commercial dent corn. Pests affective ornamental and blue corn are the same as those of other commercial corns. Ornamental and blue corns need to be grown a minimum of 500 m away from commercial yellow dent corn to minimize any cross pollination which may result in off-color kernel. Our aim in the presentation of this review was to broaden Hungarian literature.